Analisis Pembelajaran Menulis Permulaan dengan Metode SAS pada Peserta Didik Kelas I MITQ Al-Kautsar Surakarta Tahun Pelajaran 2021/2022 - Dinar Kusuma Ningrum; Anita Trisiana; Ratna Widya Ningrum (Departement of Mathematics Education, 2023)
The aims of this study were: 1) To analyze the writing difficulties experienced by students. 2) Knowing the application of the SAS (Synthetic-Structural Analytic) method in overcoming beginner writing difficulties for students. 3) Knowing the factors that influence students' initial writing difficulties. The research method used is descriptive qualitative research. The subjects used were class I MITQ Al-Kautsar Surakarta students. Data collection techniques are interviews, observation and questionnaires. Based on data analysis, the following conclusions were obtained: 1) There were six grade I students who had difficulty writing at the beginning, judging from a) the neatness of their writing; b) writing that is difficult to read; c) writing late; d) write letters upside down like b-d, p-b; e) when writing there are letters missing. 2) The implementation of the teacher's strategy in overcoming the difficulty of starting writing with the SAS method is carried out quite effectively. 3) There are two factors that influence students' initial writing difficulties, namely external factors and internal factors.